Dopamine-assisted preparation of Fe3O4@MnO2 yolk@shell microspheres for improved pseudocapacitive performance. (10th September 2019) - Chen, Qi; Wei, Wenjing; Tang, Jingjing; Lin, Jinkun; Li, Songjun; Zhu, Maiyong
Abstract: Yolk@shell nanocomposites with delicate composition and tailored structure usually exhibit great potential in various areas. In the present study, the synthesis of yolk@shell Fe3 O4 @MnO2 microspheres was reported using core@shell Fe3 O4 @polydopamine (Fe3 O4 @PDA) as starting materials. This novel approach is based on the reductive property of the PDA derived carbon shell. The new shell of MnO2 was synthesized by reaction of PDA derived carbon and KMnO4 . The Fe3 O4 @MnO2 yolk@shell microsphere was successfully used as electrode material for supercapacitor and delivers a high specific capacitance of 715 F/g at 1 A/g with a good rate capability (450 F/g at 10 A/g). Furthermore, the Fe3 O4 @MnO2 yolk@shell microsphere was also used as the positive electrode for asymmetric supercapacitors (ASC), wherein N doped carbon from PDA was applied as negative electrode. As a result, the energy density of the constructed ASC device was up to 31.3 Wh/kg at a power density of 750 W/kg. Meanwhile, the Fe3 O4 @MnO2 //N-pC (PDA derived N-doped porous carbon) device offers an excellent cycling stability (94.7% of capacitance retention after 5000 cycles). Such distinguish capacitive performance is undoubtedly related to the electrochemical actuation of the yolk@shell microsphere structure and their structural integrity, where the void between the shell and yolk may relieve the volume change of the electrode. Considering the efficiency and simplicity of the synthetic procedure, it is expected that the present method might be suitable for preparation of yolk@shell composite with other components and structures, offering potential in various applications. Graphical abstract: Image 1 Highlights: Yolk@shell structured Fe3 O4 @MnO2 micrspheres were prepared with the assistance of dopamine through a three-step process. The prepared Fe3 O4 @MnO2 microspheres show excellent electrochemical performance as supercapacitor electrode. The assembled ASC of Fe3 O4 @MnO2 //N-pC delivers a high energy density of 31.3 Wh/kg at a power density of 750 W/kg.